Selective Expression of Calcium-Binding Protein S100A7 in Lung Cancer - Hao ZHANG (Chinese Journal of Lung Cancer, 2009)
Background and objective S100A7 is a member of S100 family and its overexpression has been previously associated with carcinogenesis of certain cancers. The aim of this study is to explore the expression of calcium-binding protein S100A7 in lung cancer. Methods In the present study, RT-PCR, Western-blot and immunohistochemistry were used to analyze the different expression of S100A7 in lung cancer tissues and paired noncancerous lung tissues. Results The specific expression of S100A7 was found in squamous cell carcinomas and large cell lung carcinomas, whereas it was not detected in adenocarcinomas, small cell carcinomas, other cell types of lung cancer and normal lung tissues as well as paired noncancerous lung tissues. Conclusion S100A7 was selectively expressed in squamous cell carcinomas and large cell lung carcinomas and may serve as a potential marker for lung cancer diagnosis.